Academy of Medicine-Ministry of Health Clinical Practice Guidelines: Attention Deficit Hyperactivity Disorder - Fung, Daniel SS (Singapore Med J, 2014)
The Academy of Medicine (AMS) and the Ministry of Health (MOH) have developed the clinical practice guidelines on Attention Deficit Hyperactivity Disorder (ADHD) to provide doctors and patients in Singapore with evidence-based treatment for ADHD. This article reproduces the introduction and executive summary (with recommendations from the guidelines) from the MOH clinical practice guidelines on ADHD, for the information of SMJ readers. Chapters and page numbers mentioned in the reproduced extract refer to the full text of the guidelines, which are available from the Ministry of Health website http://www.moh.gov.sg/content/moh_web/healthprofessionalsportal/doctors/guidelines/cpg_medical.html. The recommendations should be used with reference to the full text of the guidelines. Following this article are multiple choice questions based on the full text of the guidelines.